If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8s + 4r + 13s + 6r = 0 Reorder the terms: 4r + 6r + 8s + 13s = 0 Combine like terms: 4r + 6r = 10r 10r + 8s + 13s = 0 Combine like terms: 8s + 13s = 21s 10r + 21s = 0 Solving 10r + 21s = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-21s' to each side of the equation. 10r + 21s + -21s = 0 + -21s Combine like terms: 21s + -21s = 0 10r + 0 = 0 + -21s 10r = 0 + -21s Remove the zero: 10r = -21s Divide each side by '10'. r = -2.1s Simplifying r = -2.1s
| V=x(24-2x)(24-2x) | | 2y+7-4y=-17 | | x^2+10x-200= | | 9+3*x=-6 | | 75x=2100 | | -5+24x=23x | | 10c+9v+6c-7v= | | 32=18-2k | | -191=-7-8(-5+4a) | | 5+24x=23x | | 5+24x=23 | | 3.1r=13.95 | | 7a+10b+6a-3b= | | -5+24x=23 | | 4=n+10 | | x+3=68 | | 7j+4j= | | 5x^4=5x | | 4f-8=-4n-12 | | 8+4(-8+3)=-12 | | 6+(n+7)2=25 | | (4x-16)=(2x+6) | | -6x=114 | | -4x-12y=12 | | 9u-2u= | | 7x-7=-5+2x-12 | | 6x+4=2(2x-5) | | 7c+5c= | | 1.5x-5=4x | | 2(2x-5)-3+2=x+9 | | b^3-4b^2=21b | | -16=(-x) |